Machine grinding as an alternative method for creating functional surfaces for controlling cell behaviour. Issue 1 (October 2016) - Irving, Michael; Murphy, Mark; Morgan, Mike; Lilley, Francis; French, Paul; Burton, David; Moran, Peter
Abstract There is extensive evidence to show that certain cellular behaviours including cell proliferation, migration and adhesion can be controlled by culturing cells on surfaces containing different micro-metre- and nanometre-scale features. This paper will introduce the use of machine grinding to generate surfaces with micro-sized features and their ability to affect cell behaviour. Results are presented which show that polyurethane castings of the ground surfaces can promote cell adhesion and migration. This study demonstrates the usefulness of surface grinding as a cost-effective method for generating functional surfaces for modifying cell behaviour.